2020
DOI: 10.1093/ofid/ofaa379
|View full text |Cite
|
Sign up to set email alerts
|

The Yield and Consistency of the Detection of SARS-CoV-2 in Multiple Respiratory Specimens

Abstract: Background Few studies compared the yield of the RT-PCR assay in nasopharyngeal swabs, oropharyngeal swabs, and sputum for SARS-CoV-2 detection. Method We conducted an observational study in Beijing Ditan Hospital, China. Specimens including nasopharyngeal swabs, oropharyngeal swabs and sputum from confirmed COVID-19 patients were collected for RT-PCR testing. Disease duration was calculated from the date of symptom onset to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…The systemic review and meta-analysis earlier had found sputum a better specimen than NPS and OPS [ 18 , 19 ]. A separate study by Zhang H et al [ 13 ] too found a higher detection rate of 79.2% in sputum than 37.5% and 20.8% positivity in NPS and OPS, respectively. Among sputum and OPS, Wang W et al [ 14 ] found higher positivity with sputum, whereas Chan et al [ 24 ] and Liu R et al [ 25 ] did not find any significant difference in positivity between them.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The systemic review and meta-analysis earlier had found sputum a better specimen than NPS and OPS [ 18 , 19 ]. A separate study by Zhang H et al [ 13 ] too found a higher detection rate of 79.2% in sputum than 37.5% and 20.8% positivity in NPS and OPS, respectively. Among sputum and OPS, Wang W et al [ 14 ] found higher positivity with sputum, whereas Chan et al [ 24 ] and Liu R et al [ 25 ] did not find any significant difference in positivity between them.…”
Section: Discussionmentioning
confidence: 98%
“…These studies and meta-analysis have various conclusions, probably because of analyzing a different spectrum of clinical specimens. Systemic review and meta-analysis by Bwire et al [ 17 ] and study by Wang W et al [ 14 ] reported the highest SARS-CoV-2 detection rate in BAL, while similar review and meta-analysis by Mohammadi et al [ 18 ] and study by Zhang H et al [ 13 ] recommends specimen of sputum for detection of SARS-CoV-2. Liu et al [ 10 ] and Tong et al [ 12 ] advocated NPS as specimen of choice for detection of nCoV.…”
Section: Introductionmentioning
confidence: 99%
“…LeBlanc et al 12 have reported that a combined OP and NP swab is better than only NP swab for the diagnosis of COVID-19 infection with sensitivity of 94.4 per cent (combined swab) compared to 91.7 per cent sensitivity of NP swab alone. The study by Zhang et al 13 in August 2020, with a sample size of 43 COVID-19 confirmed patients, concluded that NP and OP swabs had similar yield, and the consistency of results between OP and NP swabs was low when the disease duration was <14 days or more than 21 days. There were two studies published in 2021 14 , 15 , having the sample size of 240 and 309, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Réalisée sur un prélèvement respiratoire supérieur, la sensibilité globale de la rRT-PCR est estimée entre 32 et 90 % [24][25][26][27]. Cet intervalle très large reflète les limites méthodologiques des études (cohorte rétrospective, monocentrique, prélèvements multi sites seulement chez certains patients, délai depuis le début des symptômes non précisé) et potentiellement une qualité variable des prélèvements nasopharyngés qui nécessitent une formation du personnel préleveur.…”
Section: Selon Le Site De Prélèvementunclassified